Study of the scale effect on the resistance components and the flow field around the bulk carrier ship - عباس, نوار (Latakia University Journal -Engineering Sciences Series, 2024)
In order to create environmentally friendly ships, it is crucial to estimate the hydrodynamic behavior of the hull accurately. The main factors to consider are the ship resistance and the flow field around the ship, as these directly impact the ship's energy efficiency. Therefore, it is important to understand how the ship's scale affects its resistance components and flow field. In this study, CFD was used to conduct the numerical calculations of the bulk carrier ship at various scales at Froud number 0.142. To analyze the scale effects, the total resistance was separated into individual components. The simulation results were compared with experimental data to validate their accuracy. Finally, the hydrodynamic characteristics of the ship were studied and analyzed at different scales.